2022
DOI: 10.1051/0004-6361/202243523
|View full text |Cite
|
Sign up to set email alerts
|

Spectacular 240 kpc double-sided relativistic jets in a spiral-hosted narrow-line Seyfert 1 galaxy

Abstract: Narrow-line Seyfert 1 (NLS1) galaxies are a peculiar sub-class of active galactic nuclei (AGNe). They have demonstrated that the presence of relativistic jets in an AGN is not strictly related to its radio-loudness, the black hole mass, or their host galaxy type. Here, we present a remarkable example of a radio-quiet NLS1, 6dFGS gJ035432.8−134008 (J0354−1340). In our Karl G. Jansky Very Large Array observations at 5.5 GHz, the source shows a bright core with a flat spectral index and extended emission correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 76 publications
2
11
0
Order By: Relevance
“…Columns: (1) Function used for modelling, (2) magnitude, (3) effective radius, (4) Sérsic index, (5) axial ratio, (6) position angle, and (7) additional notes. Kotilainen et al 2016;Olguín-Iglesias et al 2017;Berton et al 2019;Olguín-Iglesias et al 2020;Hamilton et al 2021;Vietri et al 2022), and only two studies have identified elliptical galaxies (D'Ammando et al 2017(D'Ammando et al , 2018. There is some debate concerning the morphology of FBQS J1644+2619 (D'Ammando et al 2017;Olguín-Iglesias et al 2017), but the fact remains that the host galaxies of jetted NLS1 galaxies seem to preferentially be disk-like.…”
Section: Discussionmentioning
confidence: 99%
“…Columns: (1) Function used for modelling, (2) magnitude, (3) effective radius, (4) Sérsic index, (5) axial ratio, (6) position angle, and (7) additional notes. Kotilainen et al 2016;Olguín-Iglesias et al 2017;Berton et al 2019;Olguín-Iglesias et al 2020;Hamilton et al 2021;Vietri et al 2022), and only two studies have identified elliptical galaxies (D'Ammando et al 2017(D'Ammando et al , 2018. There is some debate concerning the morphology of FBQS J1644+2619 (D'Ammando et al 2017;Olguín-Iglesias et al 2017), but the fact remains that the host galaxies of jetted NLS1 galaxies seem to preferentially be disk-like.…”
Section: Discussionmentioning
confidence: 99%
“…The object exhibits an extended radio morphology with a projected size of ∼180 kpc in the VLA C-configuration observations at 5.5 GHz (see Figure A1 in Chen et al 2020). Based on the jet and counterjet flux ratio, an assumption of a jet speed of 0.5c gives a viewing angle of about 47°and a deprojected size of about 240 kpc (Vietri et al 2022), which suggest that the object is not viewed pole on, and may exclude the possibility of an underestimated BH mass due to a face-on flat BLR. The central core is unresolved on a resolution of 3 5 (∼5 kpc) and has a flux density of S 5.5 = 5.1 mJy.…”
Section: Targetmentioning
confidence: 96%
“…Mulcahy et al (2016) reported the serendipitous discovery of the double radio source of MCG+07-47-10 (J2318+4314) with a low luminosity of P 1.4GHz ∼ 10 22 W Hz −1 . Very recently, Vietri et al (2022) identified a new source J0354−1340 with the double radio lobes extending approximately 240 kpc.…”
Section: Introductionmentioning
confidence: 99%